Assessment of energy content in dog foods (2017)
ABSTRACT: Animals can regulate food intake to meet their energy demands, so the nutritional composition of the diet should be balanced with its energy density to avoid over- or under-nutrition situations. The dog food market is registering significant growth, which is reflected in a broad portfolio of products with varied energy levels; however, true quantification of their energy value is unknown. Energy needs for dogs are commonly expressed as metabolizable energy, which is estimated with mathematical approaches (indirect estimation) or determined through digestibility and metabolism trials (direct estimation). This paper reviews the energy assessment of dog food, including common methodologies and experimental procedures.